China’s paradiplomacy: a pilot study of subnational relations with neighboring countries on and off the BRI - Liu, Xuejun; Thomas, Nicholas (Frontiers in Political Science, 2025)
IntroductionA significant amount of effort and attention has been provided to China’s Belt and Road Initiative (BRI) strategy. Frequently, the existing analyses focus on the political or economic implications of China’s engagement with its BRI partners. Only recently have these state-centric analyses broadened their focus to include the roles played by subnational actors. However, even though the analytical focus of research works on China’s BRI strategy has expanded, the thematic foci on political/economic relations remains dominant. This study attempts to fill a gap in the literature by exploring social perceptions of Chinese subnational relations.MethodsCombining interviews and an original survey, this study represents an initial foray into understanding Chinese perceptions of subnational relations with countries on and off the BRI.ResultsThe findings suggest that there is a difference between how such relations are perceived, depending on the normative alignment provided by the BRI. They also indicate that shared economic interests were the most important aspect in creating a subnational partnership.DiscussionBy discussing the findings in the context of China’s strategy toward its Asian neighbors, this study strives to offer an initial evaluation of the impact of the BRI on China’s subnational relations with the neighboring countries.